95 Prevalence and Characterization of Food Insecurity in a Canadian Paediatric Emergency Department. (21st October 2022) - MacBain, Elspeth; Marjerrison, Stacey; Wahi, Gita; Eltorki, Mohamed; Pardhan, Alim; Ngo, Quang
Abstract: Background: Food insecurity (FI), defined as inadequate or insecure access to food, is a key determinant of child health. FI is associated with a number of adverse physical, psychological and developmental health outcomes and increased emergency department (ED) use. The COVID-19 pandemic has exacerbated financial hardship faced by many families with an unprecedented rise in use of charitable food programs. Objectives: We sought to determine the prevalence of FI among pediatric ED visits during the COVID-19 pandemic, compare this to pre-pandemic rates, and describe associated risk factors. Design/Methods: From September to December 2021, families presenting to a tertiary Canadian paediatric ED were asked to complete a survey screening for FI with a validated two-item questionnaire, along with socio-demographic and child health information. Results were compared to data collected in 2012. Multivariable logistic regression was used to measure associations with FI. Results: In 2021, 26% (n=173/665) of families identified as food insecure compared to 22.7% in 2012 (n=146/644), which was not statistically different (3.3%, 95% CI [-1.4%, 8.1%]). When the definition of FI is expanded to include use of charitable food assistance, the prevalence increased to 29.2%. In univariate analysis, FI was significantly associated with lack of primary care, caregivers born outside of Canada, status other than Canadian citizenship, having a child with a chronic medical condition, having financial strain related to medical expenses and reason for the ED visit being the child's chronic condition. In multivariable analysis, only having more children in the home (OR 1.19, 95% CI [1.01, 1.41]), financial strain from medical expenses (OR 5.31, 95% CI [3.45, 8.18]) and lack of primary care access (OR 1.27, 95% CI [1.08, 1.51]) remained independent predictors of FI. Approximately half (48.5%) of food insecure families reported use of food charity, most commonly food banks (31.7%), while one-quarter (26%) received help from family or friends. Food insecure families indicated their preferred means of support in hospital would be free/low cost meals and financial assistance with medical expenses. Conclusion: Greater than one in four families attending a Canadian tertiary pediatric ED screened positive for FI. FI was independently associated with lack of access to primary care, financial strain related to medical expenses, and greater number of children in the household. Further research is necessary to examine the effect of support interventions for families admitted to medical care facilities and financial support for chronic conditions.